Complaint Management Analysis variabel anteseden dan Konsekuensi: Studi Eksplorasi - Sri Hartini (Forum Manajemen Indonesia (FMI), 2016)
Goal of this research is a model of complaint handling strategy on health care institutions for the quality of service. The specific targets to be achieved are: the identification of attributes essential health services, identify performance attributes of health services, idenfifikasi complaint regarding health care received by the public, the media used in the delivery of the complaint and the complaint handling process health-care institutions. Exploratory qualitative research design used with in-dept interview to determine the behavior of the public complaint related to health care institutions and attributes of the expected public health services. To determine the relationship between variables based on qualitative research results in previous studies. model of service quality expected by society and complaint handling are ideal to create excelent service in health care institutions. The result are 4 proposition. Key words : complain handling,service excellent,layanan kesehatan